"It takes a global village": Troubling discourses of global citizenship in United Planet's voluntourism. Issue 1 (March 2015) - Zeddies, Margaret; Millei, Zsuzsa
This article merges the fields of tourism studies with the social studies of children and childhood in a discourse analysis of the voluntourism company United Planet 's website. In the past decade, United Planet has emerged as a popular voluntourist company with a mission to "unite the world in a community beyond borders." United Planet 's volunteer projects, as described on their website, combine international volunteering with cultural excursions to children living in the Global South. Through our analysis of the United Planet website and focusing on notions of childhood, we demonstrate that it constructs a seemingly harmonious transnational world that is without cultural and geographic boundaries and histories. However, the erasure of borders and historical power relations to construct a global community with a form of global citizenship attached to it hinges upon the maintenance of different trajectories and inequalities of Global North and South. In this way, this form of global citizenship contradicts United Planet, and voluntourism's promise about the creation of a more equitable world and limits its membership to the North.